Application of BOPPPS combined with dynamic scenarios simulation in ICU clinical nursing teaching (BOPPPS结合动态情景模拟在ICU护理教学中的应用) - CHEN Xi (陈曦); LI Baoyu (李宝妤); WANG Lingling (王玲玲); ZHANG Chao (张超); XIU Limin (修立敏) (中西医结合护理)
Objective To explore the application effect of BOPPPS combined with dynamic scenarios simulation in ICU nursing teaching. Methods Totally 57 nursing students who practiced their internship in ICU ward of a grade-A hospital from July, 2021 to February, 2022 were selected as the research objects. In the clinical teaching of ICU, 27 students in the control group adopted conventional teaching method, and 30 students in the experimental group adopted BOPPPS combined with dynamic scenarios simulation teaching method. The two groups were compared in terms of assessment results, independent learning ability and critical thinking level. Results The examination results of the test group were better than that of the control group, with a significant difference(P＜0. 05). The experimental group had higher evaluation on the teaching effect of BOPPPS combined with dynamic scenario simulation. After teaching, the planning and implementation, self-management and total score of independent learning ability in the experimental group were significantly higher than those of the control group, with statistical significance (P＜0. 05). There was statistically significant difference in the total score of critical thinking in experimental group before and after teaching (P＜0. 05). Conclusion BOPPPS combined with dynamic scenarios simulation can improve students' independent learning ability, cultivate students' critical thinking, and achieve good teaching effect. (目的 探讨BOPPPS结合动态情景模拟在ICU护理教学中的应用效果。方法 选取2021年7月—2022年2月在某三甲医院ICU病房实习的护理学生57名作为研究对象。在ICU的临床教学工作中, 对照组27名学生采用常规的教学方法, 试验组30名学生采用BOPPPS结合动态情景模拟教学法。比较两组学生考核成绩、自主学习能力、评判性思维水平。结果 试验组出科考核成绩优于对照组, 差异有统计学意义(P＜0. 05)。试验组学生对BOPPPS结合动态情景模拟教学效果评价较高。教学后试验组的计划和实施、自我管理及自主学习能力总分高于对照组, 差异有统计学意义(P＜0. 05); 试验组学生教学前和教学后评判性思维总分比较, 差异有统计学意义(P＜0. 05)。结论 BOPPPS结合动态情景模拟可以提高学生自主学习能力, 培养学生的评判性思维, 教学效果好。)